Polylactic acid: a review of production methods and their applications (Publicaciones en Ciencias y Tecnología, 2022)
The production of biopolymers is a subject that has gained interest due to the advantages they offer compared to plastics of petrochemical origin. One of the biopolymers with increased demand in recent years is polylactic acid. This is a non-toxic, biodegradable, compostable material with potential for use and environmental benefit compared to synthetic plastics. Given the importance that polylactic acid has gained, this review, where its properties, applications, production process and a brief dissertation of its current market is worth presenting. Based on the information consulted, polylactic acid is considered a biopolymer capable of replacing some synthetic polymers in the short and contributing to reducing the environmental impact caused by the accumulation of plastics in ecosystems. The current production of polylactic acid occupies an important position in the global market of bioplastic. It is expected that this trend of increased production will continue to satisfy the market demand for said material.
Keywords: biomaterials; biopolymers; bioplastics; PLA